ZEW Corporate Taxation Microsimulation Model (ZEW TaxCoMM) - Timo Reister; Christoph Spengel; Katharina Finke; Jost Henrich Heckemeyer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Current political discussions in Germany and other European countries illustrate the importance accorded to revenue and distribution effects of tax reforms. Whereas widely recognized concepts of effective tax measures can provide important insights into the incentives of taxation they do not allow robust revenue estimations or distribution analyses. Hence there is need to supplement existing quantitative tax models by approaches apt for these issues of policy analysis. Against this background, this paper puts forward a corporate microsimulation model allowing an ex-ante evaluation of tax reforms with regard to distributional consequences and revenue effects. Central feature of the model is the processing of financial statements included in the DAFNE data base of the Bureau van Dijk. The firm-level data is supplemented by survey data on tax accounting practices. The focus of the paper is on the documentation of the model set-up. Its application will be addressed in future publications.
More recent version: http://hdl.handle.net/10419/28006
Keywords: C15; H32; H25; D30; K34; 330; Microsimulation Model; Corporate Taxation; Policy Analysis; Firm-Level Data; Unternehmensbesteuerung; Körperschaftsteuer; Mikrosimulation; Steueraufkommen; Steuerbelastung; Steuerinzidenz; Theorie; Deutschland